An Assessment of Governance Challenges in Higher Education Institutions in Ghana. - Obeng-Sarpong, Charles; Buor, Daniel; Addo, Paul Kwadwo (Ghana Journal of Higher Education Management, 2024)
This paper explored the inherent militating issues that confront Ghanaian universities in their attempt to execute their mandate as expected. The study used both exploratory and comparative approaches to investigate challenges confronting Ghanaian universities in governance and institutional leadership. The study adopted a multi-stage sampling technique for the selection of three public and private Ghanaian universities. Anchored on Agency and Performance theories, the study focused on six (6) out of the sixty-nine (69) universities sampled. Findings indicate that externally, issues such as funding, quality assurance, linking up with the labour markets, getting requisite academics, aligning with the global trends as well as internationalisation militate against Ghanaian universities. Some operational challenges including funding (tools and logistics-related), political interferences, dealing with staff and students complaints, unapologetic stance of institutional leadership, neglecting policy feedback and policy implementation challenges also exist. The state-owned universities were found to have comparative advantage in dealing with these challenges. The study among other things, recommended governmental financial support for the private universities while decentralising operations of the supervisory bodies